Little Merchants, Big Questions: Narrative Accounts of Early Childhood Scientific Attitudes in a Traditional "Market Day" Activity - Asrul Faruq; Raharjo Raharjo; Sofa Muthohar; Rusi Novi Safitri; Izdihar Syifa Cahyani; Wan Khairul Aiman Wan Mokhtar (International Journal of Educational Narratives, 2026)
Background. Developing scientific attitudes in early childhood is important for fostering curiosity, critical thinking, problem-solving, and exploratory learning. However, learning practices in many early childhood education settings still tend to be teacher-centered, limiting children’s opportunities to engage in meaningful experiential learning. Previous studies have discussed scientific learning through experiments and play-based activities, yet research on the use of “Market Day” activities to develop scientific attitudes remains limited. Therefore, further research is needed to explore how Market Day activities can support scientific attitude development in early childhood education. Purpose. This study aims to examine how traditional market-themed “Market Day” activities facilitate the development of scientific attitudes among early childhood students, particularly through children’s participation in contextual learning processes. Method. This study employed a qualitative approach using a descriptive case study method. Participants were selected purposively and consisted of children in Groups A and B aged 5–6 years, classroom teachers, and the principal at Istiqomah Loning Petarukan Pemalang Kindergarten. Data were collected through observations, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis used the interactive model of Miles, Huberman, and Saldana. Results. The findings revealed that Market Day activities implemented through a Project-Based Learning (PjBL) approach and role-playing methods supported the development of children’s scientific attitudes. Children demonstrated curiosity, observation, questioning behavior, simple logical thinking, and communication skills through activities such as exploring goods, identifying prices, negotiating, counting money, and solving problems during transactions. The activity also promoted honesty, responsibility, numeracy skills, and early financial literacy. Conclusion. This study contributes theoretically by showing that Market Day activities can support the development of scientific attitudes through contextual and experiential learning. Practically, the findings suggest that traditional market-themed Market Day activities can be used by teachers as an effective strategy for fostering scientific attitudes and social skills in young children.